High throughput differential identification of TMPRSS2-ERG fusion genes in prostate cancer patient urine. (August 2017) - Lee, Hyojin; Lee, Dongjin; Park, Jea Ho; Song, Sang Hoon; Jeong, In Gab; Kim, Choung-Soo; Searson, Peter C.; Lee, Kwan Hyi
Abstract: Identifying genetic diversity is important for studies in cancer as it can provide insights on disease progression and treatment. Although clinical outcome and major symptom of cancer might be same in all patients, the type of overexpressed gene could be different. Even though prostate-specific antigen assay is a good tool widely used for prostate cancer diagnosis, it is not capable of providing information on genetic differences. Therefore, screening method that can differentiate genetic differences is necessary. Here we detected different types of TMPRSS2-ERG, prostate cancer specific fusion genes, to verify the genetic diversity between the patients using high throughput screening method, bio-barcode assay. Prostate cancer patients with different types of fusion gene were successfully differentiated directly from untreated patients' urine, while traditional PSA assay could not. This non-invasive assay, when used with PSA assay, can be a strong secondary screening method which can offer new insights on disease progression and clinical outcome.